On the (non) existence of a price equilibrium in delegation games with relative performance compensation - Michael Kopel; Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2012)
We show that Miller and Pazgal.s (2001) model of strategic delegation, in which managerial incentives are based upon relative performance, is affected by a non-existence problem which has impact on the price equilibrium. The undercutting incentives generating this result are indeed similar to those affecting the stability of price cartels.
Keywords: C73; L13; 330